After-School Care and Parents' Labor Supply - Christina Felfe; Michael Lechner; Petra Thiemann (Center for Economic Studies and ifo Institute (CESifo), 2013)
Does after-school care provision promote mothers' employment and balance the allocation of paid work among parents of schoolchildren? We address this question by exploiting variation in cantonal (state) regulations of after-school care provision in Switzerland. To establish exogeneity of cantonal regulations with respect to employment opportunities and preferences of the population, we restrict our analysis to confined regions along cantonal borders. Using semi-parametric instrumental variable methods, we find a positive impact of after-school care provision on mothers' full-time employment, but a negative impact on fathers' full-time employment. Thus, the supply of after-school care fosters a convergence of parental working hours.
Keywords: J13; J22; C14; 330; childcare; parents' labor supply; semi-parametric estimation methods